Enhanced bone regeneration with carbon nanotube reinforced hydroxyapatite in animal model. (July 2016) - Mukherjee, Susmita; Nandi, Samit Kumar; Kundu, Biswanath; Chanda, Abhijit; Sen, Swarnendu; Das, Pradip Kumar
Abstract: In order to improve the inherently poor mechanical properties of hydroxyapatite (HAp) and to increase its feasibility as load bearing implant material, in the present investigation, functionalised (HFC1 and HFC2 ) and non-functionalized (HC1 and HC2 ) multi-walled carbon nanotubes were used as reinforcing material with HAp. Significant improvement with respect to fracture toughness, flexural strength and impact strength of the composites was noticed. In vitro biological properties of HAp–carbon nanotube (CNT) biocomposites have also favored uniform and systematic apatite growth on their surface. Subsequently, in vivo osseous ingrowth at bone defect of rabbit femur was evaluated and compared using radiology, push out test, fluorochrome labeling, histology and scanning electron microscopy after 2 and 4 months respectively. The results demonstrated growth of web like soft callus from the host bone towards the implant, ensuring strong host bone interaction. Toxicological studies of the liver and kidney cells exhibited no abnormality, thereby confirming non-toxicity of the CNT in the animal body. Host–implant biomechanical strength showed high interfacial strength of the composites, indicating their high potentials to be used for bone remodeling applications.